Esperança Equilibrista - Resistência feminina à ditadura militar no Brasil (1964-1985). - Joffily, Olivia Rangel (2005)
This work intends to review a period in Brazilian history, the military dictatorship (1964-1985), from the point of view of the oppressed, particularly the multiple and creative ways women participated on the resistance to the military regime, showing, through interviews and bibliographic research, their path and their contribution to the establishment of democracy. It attempts to build a different version of this period of our history, reconstructing the collective and individual paths of a group of women, in permanent interaction between these two views. In this way, by giving voice to this women, it intends to contribute to the recuperation of their actions as subjects and agents of this moment in Brazilian social history. For that, were collected life stories of 12 women, who talked about their participation in support activities, in the structure of political parties, in the underground period, in exile, in armed resistance and in the solitude of imprisonment and torture.